Alpha-lipoic Acid: An Antioxidant with Anti-aging Properties for Disease Therapy - Shanaida, Mariia; Lysiuk, Roman; Mykhailenko, Olha; Hudz, Nataliia; Abdulsalam, Abdullateef; Gontova, Tetiana; Oleshchuk, Oleksandra; Ivankiv, Yana; Shanaida, Volodymyr; Lytkin, Dmytro; Bjørklund, Geir (Current Medicinal Chemistry, 2025)
The anti-aging effects of alpha-lipoic acid (αLA), a natural antioxidant synthesized in human tissues, have attracted a growing interest in recent years. αLA is a short-chain sulfur-containing fatty acid occurring in the mitochondria of all kinds of eukaryotic cells. Both the oxidized disulfide of αLA and its reduced form (dihydrolipoic acid, DHLA) exhibit prominent antioxidant function. The amount of αLA inside the human body gradually decreases with age resulting in various health disorders. Its lack can be compensated by supplying from external sources such as dietary supplements or medicinal dosage forms. The primary objectives of this study were the analysis of updated information on the latest two-decade research regarding the use of αLA from an anti-aging perspective. The information was collected from PubMed, Wiley Online Library, Scopus, ScienceDirect, SpringerLink, Google Scholar, and clinicaltrials.com. Numerous in silico, in vitro, in vivo, and clinical studies revealed that αLA shows a protective role in biological systems by direct or indirect reactive oxygen/nitrogen species quenching. αLA demonstrated beneficial properties in the prevention and treatment of many age-related disorders such as neurodegeneration, metabolic disorders, different cancers, nephropathy, infertility, and skin senescence. Its preventive effects in case of Alzheimer's and Parkinson's diseases are of particular interest. Further mechanistic and clinical studies are highly recommended to evaluate the wide spectrum of αLA therapeutic potential that could optimize its dietary intake for prevention and alleviation disorders related to aging.
Keywords: skin senescence